Latest remarks on the democracy and rule of law in CEE countries - Chyla, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Recently, most of the Central and Eastern European CEE countries are going through a very serious crisis of rule of law and constitutional democracy — especially comparing to the EU “accession period”. The apparently successful transition process, adopting the constitutional democracy and the rule of law in CEE countries is now facing serious challenges. Despite the illusive ideological solidarity, common values and increasing harmonization of law within the European Community, a contrast between the image and the reality has become visible. It turned out that apparently democratically mature new members of the European Community are, in reality, functioning in the shadows of informal networks, political systems and local correlations — while rule-of-law institutions are often too weak or underdeveloped and continuously fail to limit the abuse of uncontrolled state power. Interestingly, early signs of such shallow Europeanisation of the CEE political and legal systems has been for long marginalized by European Community. The cause of the current state is of deeply structural character, and constitutes mostly a proof of failure of defectively carried out process of transformation. The aim of the article is to present some comparative perspective on the subject and discuss the potential reasons of backsliding of CEE legal and political systems.
Keywords: rule of law; Central Eastern Europe; democracy; constitutionalism